BENDEL KESLINGMAS NO 121 TAHUN 2014 - Eka, Ima Amrizal, Dian Naeni, dkk (Buletin Keslingmas, 2014)
Malaria is one of the health problems cause of death. Mosquito longevity is an important factor to estimate the transmission. How to estimate the age of the mosquitoes with the condition of mosquito ovaries. The reseach was conducted in the seven villages malaria endemic of Banyumas Regency that is Karangsalam village, Karanggintung, Ketanda, Bogangin, Selanegara, Banjarpanepen and Watuagung to know about describe the lifetime of the mosquito Anopheles Spp in the seven villages malaria endemic, describing delatasi, parity rate, life chances and the age estimation of mosquito Anopheles Spp. The method used is descriptive by describe te lifetime of the mosquito Anopheles Spp. The data used in this research is a secondary data obtained from health center and the BPS Banyumas regency. The result showed the age estimation of Anopheles Spp mosquitos in the seven village malaria endemic that is Karangsalam, Ketanda, Selanegara, Banjarpanepen and Watuagung unknown. In the Karanggintung village the age estimation An. balabacensis mosquito is 4,24 days, whereas in the Bogangin village the age estimation An. vagus mosquito is 2,16 days. Conclusion from the research is illustration lifetime Anopheles Spp in the seven village malaria endemic is overall obatained the age estimation highest of 4,24 days is An. balabacensis mosquito. So, An. balabacensis mosquito have the ability to live in the wild longer than other Anophles Spp mosquitos were found. From the result expected for the government to increase attention to the case of malaria, especially in malaria endemic areas.